Performance Analysis of Village-Owned Enterprises Based on Financial and Management Aspects in Blitar Regency, East Java - Tri Wahyu Nugroho (HABITAT, 2020)
This study aims to analyze the performance development of village-owned enterprises (BUMDes) as the manager of productive economic activities. Performance measurement based on financial aspects and management aspects. A financial aspect includes capital growth, asset growth, asset quality, profitability. While management aspects consist of BUMDes legality, constitution, and by laws, the secretariat office, facilities, operational executor, involvement of village government in the stewardship BUMDes, incentive/honorarium board BUMDes, financial reports, progress reports, accountability BUMDes, contributions BUMDes to Government village data analysis technique used in this study is an interactive model consist of three main things: data reduction, data presentation, and conclusion. The results were obtained (1) BUMDes Health category by 84 BUMDes or 38.2%, (2) BUMDes category BUMDes Fit as many as 30 or 13.6%, (3) BUMDes category Unhealthy much as 84 BUMDes or 38.2%, (4) BUMDes category Off BUMDes as much as 22 or 10%. This implies the need for follow-up of the Government to improve performance so that it can be BUMDes BUMDes the healthy category, especially for BUMDes inactive.